2010
DOI: 10.1111/j.1365-3040.2009.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism by Cuscuta pentagona sequentially induces JA and SA defence pathways in tomato

Abstract: While plant responses to herbivores and pathogens are well characterized, responses to attack by other plants remain largely unexplored. We measured phytohormones and C18 fatty acids in tomato attacked by the parasitic plant Cuscuta pentagona, and used transgenic and mutant plants to explore the roles of the defence-related phytohormones salicylic acid (SA) and jasmonic acid (JA). Parasite attachment to 10-day-old tomato plants elicited few biochemical changes, but a second attachment 10 d later elicited a 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 82 publications
1
52
0
2
Order By: Relevance
“…Thus, it can be hypothesized that parasitic plants recruit defense-related genes for host recognition. Considering that a host may demonstrate active defense responses to dodder attack (Runyon et al, 2010), it also appears that the parasite is under biotic stress and, hence, may recruit its own defense mechanism to overcome the counterattack.…”
Section: Recruitment Of Genes Relating To Responses To Stimuli and Cementioning
confidence: 99%
“…Thus, it can be hypothesized that parasitic plants recruit defense-related genes for host recognition. Considering that a host may demonstrate active defense responses to dodder attack (Runyon et al, 2010), it also appears that the parasite is under biotic stress and, hence, may recruit its own defense mechanism to overcome the counterattack.…”
Section: Recruitment Of Genes Relating To Responses To Stimuli and Cementioning
confidence: 99%
“…The root parasite Orobanchae ramose induced JA-dependent genes but not SA-dependent genes in Arabidopsis (Dos Santos et al 2003). As for Cuscuta, only one previous study by Runyon et al (2010) suggested that both JA and SA responded after Cuscuta pentagona parasitization of tomatoes (Solaum lycopersicum), and the JA peak was prior to SA. In our Cuscuta-Momordica interaction, JA was not changed but SA was increased in Momordica.…”
Section: Plant Hormonal Changes In Momordicamentioning
confidence: 99%
“…Previously, Runyon et al (2010) found hypersensitive-like response (HLR) in tomatoes (Solaum lycopersicum), which was provoked by Cuscuta pentagona. HLR was observed only in 20-day-old tomatoes (both at hypocotyls and petiole).…”
Section: Introductionmentioning
confidence: 99%
“…Parasitic plants make their living by extracting resources from other plants and, therefore, share many of the same ecological challenges faced by other plantfeeding organisms, including the need to acquire appropriate hosts and overcome host defenses (Runyon et al, 2006(Runyon et al, , 2008(Runyon et al, , 2010Mescher et al, 2009;Smith et al, 2009). In the case of arthropod herbivores, many species are able not only to overcome the chemical defenses of their hosts but also to sequester plant toxins for use against their own natural enemies (Opitz and Mueller, 2009).…”
mentioning
confidence: 99%